Proprioceptive drift in the rubber hand illusion is intensified following 1 Hz TMS of the left EBA - Wold, Andrew; Limanowski, Jakub; Walter, Henrik; Blankenburg, Felix (Frontiers in Human Neuroscience, 2014)
The rubber hand illusion (RHI) is a paradigm used to induce an illusory feeling of owning a dummy hand through congruent multisensory stimulation. Thus, it can grant insights into how our brain represents our body as our own. Recent research has demonstrated an involvement of the extrastriate body area (EBA), an area of the brain that is typically implicated in the perception of non-face body parts, in illusory body ownership. In this experiment, we sought causal evidence for the involvement of the EBA in the RHI. Sixteen participants took part in a sham controlled, 1 Hz repetitive transcranial magnetic stimulation (rTMS) experiment. Participants received (RHI condition) or asynchronous (control) stroking and were asked to report the perceived location of their real hand, as well as the intensity and the temporal onset of experienced ownership of the dummy hand. Following rTMS of the left EBA, participants misjudged their real hand’s location significantly more toward the dummy hand during the RHI than after sham stimulation. This difference in “proprioceptive drift” provides the first causal evidence that the EBA is involved in the RHI and subsequently in body representation and further supports the view that the EBA is necessary for multimodal integration.